Activin Receptor Ligand Blocking and Cancer Have Distinct Effects on Protein and Redox Homeostasis in Skeletal Muscle and Liver - Hentilä, Jaakko; Nissinen, Tuuli A.; Korkmaz, Ayhan; Lensu, Sanna; Silvennoinen, Mika; Pasternack, Arja; Ritvos, Olli; Atalay, Mustafa; Hulmi, Juha J. (Frontiers in Physiology, 2019)
Muscle wasting in cancer cachexia can be alleviated by blocking activin receptor type 2 (ACVR2) ligands through changes in protein synthesis/degradation. These changes in cellular and protein metabolism may compromise protein homeostasis. First, we elucidated the acute (1–2 day) and 2-week effects of blocking ACVR2 ligands by soluble activin receptor 2B (sACVR2B-Fc) on unfolded protein response (UPR), heat shock proteins (HSPs) and redox balance in skeletal muscle. Second, the effects of C26 cancer-induced cachexia on UPR, autophagy and redox balance with or without sACVR2B-Fc were examined. Skeletal muscle and the liver were collected 11 days after the cancer cell inoculation. sACVR2B-Fc had no effect on UPR indicators nor on heat shock proteins 1–2 days after a single administration in the muscles of healthy mice, but protein carbonyls increased (p < 0.05). After 2 weeks of sACVR2B-Fc administration, muscle size was increased, accompanied by increased UPR markers: GRP78 (p < 0.05), phosphorylated eIF2α (p < 0.01) and HSP47 (p < 0.01). Additionally, protein carbonyls and reduced form of glutathione increased (GSH) (p < 0.05). On the other hand, in skeletal muscle of tumor-bearing mice, UPR markers p-eIF2α, HSP47, p-JNK (p < 0.05) and antioxidant GSH decreased, whereas the ratio of oxidized to reduced glutathione increased (GSSG/GSH; p < 0.001). Administration of sACVR2B-Fc in tumor-bearing mice prevented the decline in GSH and increased some of the UPR indicators. Additionally, autophagy markers LC3II (p < 0.05) Beclin-1 (p < 0.01) and P62 (p < 0.05) increased. In the liver of tumor-bearing mice, UPR indicators PERK, p-eIF2α and GRP78 increased (p < 0.05), whereas ATF4 was strongly decreased (p < 0.01) sACVR2B-Fc having no effect. Many of the altered UPR indicators in the liver and muscle as well as muscle GSH correlated with tumor mass, fat mass and body weight loss. In conclusion, muscle hypertrophy induced by blocking ACVR2B ligands may induce UPR and increase protein carbonyls, but it may also upregulate antioxidant protection in experimental cancer. Cancer cachexia is accompanied by distinct and tissue-specific changes in proteostasis that are associated with the severity of the cachexia.